Computer Vision Based Hand Gesture Recognition For Speech Disabled Persons - Acharya, Manoj; Pant, Dibakar Raj (Journal of the Institute of Engineering, 2016)
This paper proposes a method to recognize static hand gestures in an image or video where a person is performing Nepali Sign Language (NSL) and translate it to words and sentences. The classification is carried out using Neural Network where contour of the hand is used as the feature. The work is verified successfully for NSL recognition using signer dependency analysis. Journal of the Institute of Engineering, 2015, 11(1): 30-35